Unravelling Disorder Effects on Thermoelectric Properties of Semicrystalline Polymers in a Wide Range of Doping Levels. Issue 2 (28th November 2022) - Choi, Woojin; Kim, Soohyun; Lee, Soonyong; Jung, Changhwa; Tripathi, Ayushi; Lee, Yoonjoo; Woo, Han Young; Lee, Hyunjung
Abstract: Thermoelectric (TE) performance of a specific semicrystalline polymer is studied experimentally only in a limited range of doping levels with molecular doping methods. The doping level is finely controlled via in situ electrochemical doping in a wide range of carrier concentrations with an electrolyte ([PMIM] + [TFSI] − )‐gated organic electrochemical transistor system. Then, the charge generation/transport and TE properties of four p‐type semicrystalline polymers are analyzed and their dynamic changes of crystalline morphologies and local density of states (DOS) during electrochemical doping are compared. These polymers are synthesized based on poly[(2, 5‐bis(2‐alkyloxy)phenylene)‐alt‐(5, 6‐difluoro‐4, 7‐di(thiophene‐2‐yl)benzo[ c ][1, 2, 5]thiadiazole)] by varying side chains: With oligoethylene glycol (OEG) substituents, facile p‐doping is achieved because of easy penetration of TFSI − ions into the polymer matrix. However, the charge transport is hindered with longer OEG chains length because of the enhanced insulation. Therefore, with the shortest OEG substituents the electrical conductivity (30.1 S cm −1 ) and power factor (2.88 µW m −1 K −2 ) are optimized. It is observed that all polymers exhibit p‐ to n‐type transition in Seebeck coefficients in heavily doped states, which can be achieved by electrochemical doping. These TE behaviors are interpreted based on the relation between the localized DOS band structure and molecular packing structure during electrochemical doping. Abstract : In situ charge generation, transport, and thermoelectric properties of a series of side chain‐engineered semicrystalline polymers are studied by electrochemical doping using an electrolyte‐gated organic electrochemical transistor system. The detailed characteristics on the morphological and localized density of states variation, and transition from p‐ to n‐doped states by doping are discussed.